2011
DOI: 10.1038/nrmicro2636
|View full text |Cite
|
Sign up to set email alerts
|

Growth of Candida albicans hyphae

Abstract: The fungus Candida albicans is often a benign member of the mucosal flora; however, it commonly causes mucosal disease with substantial morbidity and in vulnerable patients it causes life-threatening bloodstream infections. A striking feature of its biology is its ability to grow in yeast, pseudohyphal and hyphal forms. The hyphal form has an important role in causing disease by invading epithelial cells and causing tissue damage. This Review describes our current understanding of the network of signal transdu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

21
978
3
31

Year Published

2012
2012
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 934 publications
(1,033 citation statements)
references
References 139 publications
21
978
3
31
Order By: Relevance
“…Real‐time PCR analysis showed that exogenous addition of the leading compound 28e inhibited the expression levels of CDC35, EFG1, TEC1 and HWP1, which are regulators involved in the cAMP‐PKA pathways (Fig. 6C and D) (Sudbery, 2011). In addition, some regulators of the MAPK cascade (Zhao et al ., 2013), such as HST7, CEK1 and CPH1, were also downregulated by the exogenous addition of compound 28e (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Real‐time PCR analysis showed that exogenous addition of the leading compound 28e inhibited the expression levels of CDC35, EFG1, TEC1 and HWP1, which are regulators involved in the cAMP‐PKA pathways (Fig. 6C and D) (Sudbery, 2011). In addition, some regulators of the MAPK cascade (Zhao et al ., 2013), such as HST7, CEK1 and CPH1, were also downregulated by the exogenous addition of compound 28e (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Since FLZ interferes with the ergosterol pathway and ergosterol is necessary for hyphae formation, the presence of FLZ inhibits the transition from yeast to hypha [48], even in a culture medium that promotes C. albicans filamentous morphology. Thus, taking into consideration that hypha is the invasive form of C. albicans [49], the reduction of its size in both CaS and CaR is an important result in the decrease of the virulence of this strain. In addition, FLZ significantly reduced the CFU/mL in CgS and CgR (Figure 2).…”
Section: Discussionmentioning
confidence: 99%
“…The success of C. albicans as a major fungal pathogen of humans relies on a number of pathogenic traits, among which its capacity to grow and switch between at least three distinctive morphological forms: budding yeast, pseudohyphae and hyphae [2][3][4][5]. The morphogenetic transition has been commonly described as a critical trait for survival and virulence in the host, even though the analysis of a wide array of C. albicans knock-out mutants suggests that pathogenesis can be dissociated to some extent from morphological switching [6][7][8].…”
Section: Introductionmentioning
confidence: 99%